DAMPAK PENGGUNAAN GADGET PADA PERKEMBANGAN EMOSI SISWA DI SDN 67 BANGKUDU KAB. LUWU - Lusiani; Kadir, Abdul; Suarja, Septya; Bin Anuar, Arman (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2025)
Gadgets are one of the electronic objects that develop so quickly among everyone, both adults and children. The background of this study is based on the rampant use of gadgets by elementary school children, which can affect aspects of their emotional development, both positively and negatively. This study aims to determine the impact of gadget use on students' emotional development at SDN 67 Bangkudu and the factors of gadget use that affect students' emotional development at SDN 67 Bangkudu. This study uses qualitative research methods with student subjects at SDN 67 Bangkudu. The results showed that the Impact of Gadget Use on Student Emotions at SDN 67 Bangkudu uses gadgets a lot to play online games, especially Free Fire, as well as social media such as TikTok and Instagram. This intensive use risks causing addiction and disturbances in emotional, health and educational aspects. As well as Factors Affecting Students' Emotional Development due to Gadgets The three aspects of emotions that are affected are anger, empathy, and social interaction.